The scientific production process of San Marcos University medical school researchers - Sogi, Cecilia (2002)
OBJECTIVE: To identify personal, institutional and contextual factors involved in the scientific papers production process by Medical School researchers. MATERIAL AND METHODS: 1) The San Marcos University Research Activities Registry (RAIS) data base created by the Research Council (CSI); and 2) In depth interviews of intentionally selected informers inquiring about various aspects of the scientific production process. RESULTS: During the period 1990 through 2001 from 994 faculty members, 149 (15%) published scientific papers in journals and registered them in the RAIS. Their profile was: males 62%; mean age 58; physicians 2 out of 3; with Doctor or Master Degree and either exclusive dedication or full time faculty 1 of every 2; attached to Research Center/ Institute 60%. The interviews qualitative analysis highlighted the consensus that scientific studies results should be published, but requirement of minimal material and social conditions was not always satisfied by the university. CONCLUSIONS: Production of scientific papers varies among Medical School researchers, and various limiting factors were appreciated. The university should consider process pecularities and correct interferences by releasing specific norms.